Reconstruction of Islamic Institution Education the 21st Hopes, Challenges, Paradigms, and Roles of Arabic - Asril, Zainal; Hanafi, Abdul Halim (Institut Agama Islam Negeri Imam Bonjol Padang, 2021)
This research aims to describe the problems are how the position, condition, standardization, accusation, and protection of Islamic institutions higher education to services customer’s or student in Indonesia and how is learning system and developing science in this age and challenges facing Islamic institution of higher education and the expectations and strategies to deal accretion. The method uses library research, observation to document, literature, discussion, and interview with experts about LPTI. The research finding is the 21st century is the age globalization. It takes to impact on interdependencies, competition, and advances in science, information and communication technology on institution of Islamic higher education. Interdependention describe the something happened in a country correlated with other country. This condition has to change of paradigm at management of institution higher education that the society make it is corporate has to protects and the best accusation and quickly services to customers. The conclusion are (1) the expectation that Islamic higher education must remain firm lying to the main foundations, the Qur'an and Hadith, and pay attention to and strengthen the teaching of Arabic and must be able to prove the truth of the foundation in human/community life and in addition to (2) Islamic higher educational must enter the official level of quality standards, and in the end (3) Islamic higher education make themselves as higher education research that aims to change the real (research to cange of emancipartory). It can be done from simple ways